2015
DOI: 10.14260/jemds/2015/22
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cecal Diverticulum in a Child

Abstract: A 12-year-old girl with abdominal pain and fever underwent urgent surgery. As was suspected 15 on computed tomographic scan, a large diverticular mass adherent to the cecum was identified. A 16 diverticulectomy was performed. We report this rare case of a giant cecal diverticulum and provide an 17 overview of known literature. Acute abdominal pain is a very common reason for 21 consulting a pediatric surgical emergency care unit. 22However, the diagnostics and treatment can be challenging. Because of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Detorsion was done and diverticulectomy performed. Ramu et al, (2015) reported a case of a 11-yearold girl with an acute abdomen (7). A 15 cm long, 5 cm diameter caecal diverticulum attached to the lateral and inferior aspect of the caecum was discovered with a faecolith.…”
Section: Discussionmentioning
confidence: 99%
“…Detorsion was done and diverticulectomy performed. Ramu et al, (2015) reported a case of a 11-yearold girl with an acute abdomen (7). A 15 cm long, 5 cm diameter caecal diverticulum attached to the lateral and inferior aspect of the caecum was discovered with a faecolith.…”
Section: Discussionmentioning
confidence: 99%